Fisetin may protect early porcine embryos from oxidative stress by down-regulating GRP78 levels - Xiu-Wen Yuan; Hao Guo; ChaoRui Wang; HeWei Ji; YongNan Xu; Xue Rui Yao; Lin Wang; QiLong Cao; Nam-Hyung Kim; Ying-Hua Li (PeerJ)
Fisetin is a natural flavonol with a variety of biological activities, including anti-inflammatory and antitumor activities. However, the effect of fisetin on mammalian oocyte and embryo development is unknown, so in this study, we used porcine oocytes as an experimental model, and added optimal concentrations of fisetin to the in vitro culture medium after parthenogenetic activated to investigate the effect of fisetin on porcine embryo development. It was found that 0.1 µM fisetin significantly increased the cleavage rate and blastocyst formation rate, and the quality of blastocysts was also improved. Staining results showed that the levels of reactive oxygen species (ROS), autophagy, endoplasmic reticulum stress and apoptosis were significantly reduced, while glutathione levels and mitochondrial function were significantly increased in the 0.1 µM fisetin-treated group of early porcine embryos compared with the control group. Meanwhile, fisetin decreased the expression level of the endoplasmic reticulum stress marker protein GRP78 (0.71 ± 0.19). In addition, fisetin decreased the expression of genes related to pro-apoptosis, autophagy and endoplasmic reticulum stress and increased the expression of genes related to antioxidant, pluripotency and mitochondrial. According to our results, fisetin promotes early embryonic development in porcine, and this effect may be realized by down-regulating the expression level of GRP78.